Impact of Recruitment and Selection Practices on Teaching Faculties Satisfaction at Community Colleges of Nepal - Mainali, Hari Lal; Verma, Sudhanshu (International Research Journal of MMC, 2021)
The process of attracting, evaluating, and hiring individuals for an organization is known as recruitment. Selection is the process of identifying an individual from a pool of job applicants with the requisite qualifications and competencies to fill jobs in the organization. The purpose of this paper is to explore the effects of recruitment and selection practices on teaching faculty satisfaction in community colleges. The researcher adopted a Qual-Quan approach with a descriptive and cross-sectional research design. A structured questionnaire was applied for quantitative information collection from 49 respondents, and an FGD was conducted to collect qualitative information. Stratified and random sampling techniques were used to select the sample from the targeted population, and data processing was done using SPSS version 26. In order to reach a conclusion, ANOVA, Chi-square and frequency statistical tools were used for data analysis. The analyses showed there was a significant impact of recruitment and selection practices on teaching faculty satisfaction in community colleges of Nepal.